Effect of Pore-Scale Mineral Spatial Heterogeneity on Chemically Induced Alterations of Fractured Rock: A Lattice Boltzmann Study - Hossein Fazeli; Ravi Patel; Helge Hellevang (Geofluids)
Fractures are the main flow path in rocks with very low permeability, and their hydrodynamic properties might change due to interaction with the pore fluid or injected fluid. Existence of minerals with different reactivities and along with their spatial distribution can affect the fracture geometry evolution and correspondingly its physical and hydrodynamic properties such as porosity and permeability. In this work, evolution of a fracture with two different initial spatial mineral heterogeneities is studied using a pore-scale reactive transport lattice Boltzmann method- (LBM-) based model. The previously developed LBM transport solver coupled with IPHREEQC in open-source Yantra has been extended for simulating advective-diffusive reactive transport. Results show that in case of initially mixed structures for mineral assemblage, a degraded zone will form after dissolution of fast-dissolving minerals which creates a resistance to flow in this region. This causes the permeability-porosity relationship to deviate from a power-law behavior. Results show that permeability will reach a steady-state condition which also depends on transport and reaction conditions. In case of initially banded structures, a comb-tooth zone will form and the same behavior as above is observed; however, in this case, permeability is usually less than that of mixed structures.